Influence of Pollution on Diversity and Nutritional Composition of Aquatic Edible Insects from Lake Victoria, Kenya - Misiko, Monicah Florence (JOOUST, 2024)
Freshwater pollution has become a significant global environmental issue, impacting biodiversity and ecosystem services. Winam Gulf of Lake Victoria is greatly affected by pollution from human activities and natural forces. However, little is known about the impacts of pollution on the diversity and nutritional value of edible insects in Winam gulf. This study was therefore conducted with the main objective of determining the effect of pollution on the diversity and nutritional status of the aquatic insects, particularly Chironomus species inhabiting Winam Gulf. The targets of the study included understanding the quality of water, how it impacts the distribution and genetic variation of insects, and the impact of pollution on the nutritional value of aquatic insects. 6 sampling stations were established within Winam Gulf: Kisumu Bay, Kendu Bay, Homa Bay, Maboko and Ndere Islands, and several fish landing beaches. Pollutants like heavy metals (arsenic, mercury, lead, and cadmium), nutrients (NH4-N, NO3-N, NO2-N, TN, TP, PO4-P), physic-chemical parameters (temperature, pH, conductivity, dissolved oxygen, and turbidity) were analyzed from water and sediment samples. Morphological and molecular approaches used, and the indices of Simpson, Shannon-Weaver, and Pielou’s calculated in studying the diversification of aquatic insects. Their genetic variation was measured using the molecular marker from the CO1 gene, and nutritional content, including amino acids, vitamins, fatty acids, micronutrients and macronutrients determined using spectrophotometric analysis. Data analysed, expressed Mean ±SE. Analysis of Variance (ANOVA), Tukey’s post hoc test employed. Associations between variables analyzed by Pearson's Correlation Coefficient, Canonical Correspondence Analysis (CCA), and Principal Component Analysis (PCA). The results revealed significant differences in water quality parameters at the six stations. Specifically, Kisumu Bay and Homa Bay recorded a relatively high level of pollutants, NO2, NO3, PO4-P, and heavy metals, compared to other areas like, Maboko and Ndere Islands, more isolated from human activities, exhibited lower pollution levels. 383 aquatic insects were captured, comprising 6 orders, 16 families, 19 genera and 19 species. The highest diversity was observed in Kisumu Bay, despite high pollution levels, suggesting the presence of pollution- tolerant species. Chironomus spp. dominated the insect community in more polluted sites, indicating their resilience to environmental stress. Molecular analysis identified three Chironomus species: Chironomus transvaalensis (Kisumu Bay), Chironomus pseudothummi (Kendu Bay and Homa Bay). In contrast, another unidentified species was found in Ndere Island. This means these species were diverse genetically, showing their adaptability to pollution. Amino acid concentrations varied significantly across sites, with arginine, valine, methionine, and isoleucine showing higher levels in less polluted areas -Ndere Island. Pollution resulted in changes in the fatty acid profile, with palmitic, stearic, and oleic acids, abundant, with significant differences in concentration between polluted and less polluted sites. Omega-3 and omega-6 fatty acids were detected though in smaller quantities, in more polluted zones, indicating the effect of pollution on nutritional quality of Chironomus spp. Finally, the study ascertained that pollution significantly impacts both the diversity and nutritional status of Chironomus spp.in Lake Victoria. Despite this, Chironomids, as bio indicators, showed resilience to pollution, but their nutritional quality, particularly fatty acids and amino acids, was compromised in highly polluted sites which had implications on safety and nutritional value as a food source. Hence, the urgent need for pollution management and recommended continuous monitoring of water quality, adoption of sustainable practices to reduce pollution and suggested the potential for cultivating Chironomids in controlled environments to ensure their safety as an alternative food source, contributing to food security in the region. has become a significant global environmental issue, impacting biodiversity and ecosystem services. Winam Gulf of Lake Victoria is greatly affected by pollution from human activities and natural forces. However, little is known about the impacts of pollution on the diversity and nutritional value of edible insects in Winam gulf. This study was therefore conducted with the main objective of determining the effect of pollution on the diversity and nutritional status of the aquatic insects, particularly Chironomus species inhabiting Winam Gulf. The targets of the study included understanding the quality of water, how it impacts the distribution and genetic variation of insects, and the impact of pollution on the nutritional value of aquatic insects. 6 sampling stations were established within Winam Gulf: Kisumu Bay, Kendu Bay, Homa Bay, Maboko and Ndere Islands, and several fish landing beaches. Pollutants like heavy metals (arsenic, mercury, lead, and cadmium), nutrients (NH4-N, NO3-N, NO2-N, TN, TP, PO4-P), physic-chemical parameters (temperature, pH, conductivity, dissolved oxygen, and turbidity) were analyzed from water and sediment samples. Morphological and molecular approaches used, and the indices of Simpson, Shannon-Weaver, and Pielou’s calculated in studying the diversification of aquatic insects. Their genetic variation was measured using the molecular marker from the CO1 gene, and nutritional content, including amino acids, vitamins, fatty acids, micronutrients and macronutrients determined using spectrophotometric analysis. Data analysed, expressed Mean ±SE. Analysis of Variance (ANOVA), Tukey’s post hoc test employed. Associations between variables analyzed by Pearson's Correlation Coefficient, Canonical Correspondence Analysis (CCA), and Principal Component Analysis (PCA). The results revealed significant differences in water quality parameters at the six stations. Specifically, Kisumu Bay and Homa Bay recorded a relatively high level of pollutants, NO2, NO3, PO4-P, and heavy metals, compared to other areas like, Maboko and Ndere Islands, more isolated from human activities, exhibited lower pollution levels. 383 aquatic insects were captured, comprising 6 orders, 16 families, 19 genera and 19 species. The highest diversity was observed in Kisumu Bay, despite high pollution levels, suggesting the presence of pollution- tolerant species. Chironomus spp. dominated the insect community in more polluted sites, indicating their resilience to environmental stress. Molecular analysis identified three Chironomus species: Chironomus transvaalensis (Kisumu Bay), Chironomus pseudothummi (Kendu Bay and Homa Bay). In contrast, another unidentified species was found in Ndere Island. This means these species were diverse genetically, showing their adaptability to pollution. Amino acid concentrations varied significantly across sites, with arginine, valine, methionine, and isoleucine showing higher levels in less polluted areas -Ndere Island. Pollution resulted in changes in the fatty acid profile, with palmitic, stearic, and oleic acids, abundant, with significant differences in concentration between polluted and less polluted sites. Omega-3 and omega-6 fatty acids were detected though in smaller quantities, in more polluted zones, indicating the effect of pollution on nutritional quality of Chironomus spp. Finally, the study ascertained that pollution significantly impacts both the diversity and nutritional status of Chironomus spp.in Lake Victoria. Despite this, Chironomids, as bio indicators, showed resilience to pollution, but their nutritional quality, particularly fatty acids and amino acids, was compromised in highly polluted sites which had implications on safety and nutritional value as a food source. Hence, the urgent need for pollution management and recommended continuous monitoring of water quality, adoption of sustainable practices to reduce pollution and suggested the potential for cultivating Chironomids in controlled environments to ensure their safety as an alternative food source, contributing to food security in the region.
Keywords: Pollution; Aquatic Edible Insects; Lake Victoria, Kenya; Insects; Freshwater pollution